Studies on Correlation and Path Analysis for Yield and Morpho-Physiological Traits in Elite Rice (Oryza sativa L.) Genotypes under Dry DSR System - Md. Farheen,; Murthy, K. Gopala Krishna; Mohan, Y. Chandra; Kumar, J. Hemantha (International Journal of Bio-resource and Stress Management, 2023)
An experiment was conducted at the Agricultural College, Aswaraopet, Bhadradri Kothagudem district, Telangana, India during July to December 2021 by using thirty elite rice genotypes comprising of different durations i.e. short, medium and long to study the nature of relationship between grain yield and morpho-physiological traits by partitioning the correlation co-efficients between grain yield and morpho-physiological traits into direct and indirect effects. Observations were recorded on seven yield, six physiological and three root characters. The correlation studies revealed that, grain yield plant-1 had shown a significant positive association with yield contributing traits like 1000 grain weight, spikelet fertility, specific leaf area and root biomass, indicating the importance of these traits in yield improvement. Among all other yield attributing characters, spikelet fertility showed the highest significant positive correlation with yield whereas days to 50% flowering and number of productive tillers plant-1 exhibited non-significant positive association with grain yield plant-1. Path coefficient analysis revealed that the highest positive direct effect on grain yield was exhibited by spikelet fertility and 1000 grain weight. A high magnitude of negative direct effects on yield was shown by field emergence at 14 DAS. Thus, from the studies on correlation and path analysis, it could be concluded that the traits viz., spikelet fertility, 1000 grain weight, specific leaf area and root biomass could be used as selection parameters for improving grain yield under dry DSR system.